Effects of combined aerobic dance exercise and honey supplementation on bone metabolism and muscular strength in women - Rahim, Marhasiyah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Abstract. Although combination of physical activity with supplementation has being investigated on its effects in maintaining and enhancing bone health, however little is known about the effectiveness of combination of aerobic dance exercise and honey supplementation on bone metabolism markers and muscular strength in women. The aim of this study was to investigate the effects of combined aerobic dance exercise and honey supplementation on bone metabolism and muscular strength in women. Forty four subjects. healthy sedentary women (25-40 year-old) were age and weight matched, and subsequently being assigned into four groups with n=ll per group: Control group (C), honey supplementation group (H), aerobic dance exercise group (Ex) and combined aerobic dance exercise with honey supplementation group (HEx). Aerobic dance exercise was carried out for one hour per session, three times per week for eight weeks. Honey drink was consumed by H and HEx groups, in a dosage of 20g of honey diluted in 300m! of plain water, for 7 days per week for a total of 8 weeks duration. In HEx group, the subjects were required to consume honey drink 30 minutes before performing exercise on the exercise days. Before and after 8 weeks of experimental period, subjects' right lower limb muscular strength were measured with knee extension and flexion isokinetic peak torque at 180 and 300 degree per second. Meanwhile, blood samples were taken in order to determine the concentrations of serum total calcium, osteocalcin (bone formation marker), serum C-terminal telopeptide of type I collagen (ICTP) (bone resorption marker), and parathyroid hormone (PTH). At the end of 8 weeks of experimental period, combination of aerobic dance exercise with honey supplementation (HEx) exhibited more discemable beneficial effects on lower limb peak torque compared to the other three Ex, H and C groups. Regarding bone metabolism, the percentage of increment in I CTP, a bone resorption marker, and PTH concentrations in HEx group were the lowest compared to the other experimental groups. The results of present study suggest that combination of aerobic dance exercise and honey supplementation may elicit effects on reducing the increment in bone resorption, and more beneficial effects on lower limb muscular strength compared to aerobic dance exercise or honey supplementation alone in sedentary women.